Moderate Aerobic Training Improves Cardiorespiratory Parameters in Elastase-Induced Emphysema - Henriques, Isabela; Lopes-Pacheco, Miquéias; Padilha, Gisele A.; Marques, Patrícia S.; Magalhães, Raquel F.; Antunes, Mariana A.; Morales, Marcelo M.; Rocha, Nazareth N.; Silva, Pedro L.; Xisto, Débora G.; Rocco, Patricia R. M. (Frontiers in Physiology, 2016)
Aim: We investigated the therapeutic effects of aerobic training on lung mechanics, inflammation, morphometry and biological markers associated with inflammation and endothelial cell damage, as well as cardiac function in a model of elastase-induced emphysema. Methods: Eighty-four BALB/c mice were randomly allocated to receive saline (control, C) or 0.1 IU porcine pancreatic elastase (emphysema, ELA) intratracheally once weekly for 4 weeks. After the end of administration period, once cardiorespiratory impairment associated with emphysema was confirmed, each group was further randomized into sedentary (S) and trained (T) subgroups. Trained mice ran on a motorized treadmill, at moderate intensity, 30 min/day, 3 times/week for 4 weeks. Results: Four weeks after the first instillation, ELA animals, compared to C, showed: 1) reduced static lung elastance (Est,L) and levels of vascular endothelial growth factor (VEGF) in lung tissue, 2) increased elastic and collagen fiber content, dynamic elastance (E, in vitro), alveolar hyperinflation, and levels of interleukin-1β and tumor necrosis factor (TNF)-α, and 3) increased right ventricular diastolic area (RVA). Four weeks after aerobic training, ELA-T group, compared to ELA-S, was associated with reduced lung hyperinflation, elastic and collagen fiber content, TNF-α levels, and RVA, as well as increased Est,L, E, and levels of VEGF. Conclusion: Four weeks of regular and moderate intensity aerobic training modulated lung inflammation and remodeling, thus improving pulmonary function, and reduced RVA and pulmonary arterial hypertension in this animal model of elastase-induced emphysema.